Preparation and property of soluble hemostatic material with 3D knitted structure. (30th June 2022) - Zhang, Shiyao; Shi, Tingting; Wu, Guangjun; Zhang, Qi; Ma, Pibo
To solve the problems of low mechanical properties and poor coagulation effect of soluble hemostatic dressings, a new type of soluble hemostatic fabric with three-dimensional knitted structure is proposed in this paper. Three-dimensional knitted fabrics had good extension and porous structure. This three-dimensional soluble knitted fabric can be used for skin wounds clotting and healing. This paper mainly studied the influence of structural thickness on the performance of three-dimensional knitted dressings. Characterization analysis showed that three-dimensional knitted soluble hemostatic dressings had appropriate porosity and water vapor transmission rate (WVTR), and the fabric with the maximum thickness had good elongation (70.04%) and a very low blood clotting index (BCI) (11.18%). This suggests the potential application for soluble three-dimensional knitted structure fabric on skin wound hemostasis.